FACIES MODELING OF PRABU RESERVOIR IN SEVILLA FIELD, WEST NATUNA BASIN - , Reza Satria Nugraha ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In geomodeling, the facies modeling phase has always been the most challenging part because it will later act as the container for properties such as porosity, permeability, and water saturation to be populated in. There are uncertainties in interpreting the facies association interpretation, the conceptual model, creating the electrofacies that has good correlation with log responses to ensure facies to properties consistency, and distributing the facies laterally and vertically. All of these issues have impact to the reservoir connectivity, the volumetric uncertainty, properties distribution and cause difficulties in finding remaining potential and infill drilling locations. Data used in this research are basically core data, log data, seismic data, and production data. There are 17 wells with standard logs were used in this research. Core data is of 170 feet measured depth (MD) long. It is in good condition with almost 100% recovery. Input from seismic data such as faults and horizons interpretation will be taken to the structural framework and 3D grid building for modeling purpose. The attribute map will be used as guidance for the sand fairway. The production data is taken from the 4 producing wells that perforated in Prabu zone. The new model from this thesis can represent the well interference between well A10 to well A07 and well A06. The model can also explain why well A06 response better than well A07 to gas injection from well A05.